‘Do it afraid’: An arts‐based reflexive collective case study exploring youth responses to post‐concussion communication changes in daily life - Harasym, Jessica A.; Gross, Douglas P.; MacLeod, Andrea A. N.; Phelan, Shanon K. (International journal of language & communication disorders, 2024)
Background Concussion and communication researchers have yet to study how post‐concussion communication changes affect youths’ daily lives. The lack of attention paid to how young people respond to communication changes during concussion recovery constitutes a significant gap in current concussion management research and practices. Aims To explore how youth respond to the effects of post‐concussion communication changes in their daily life, including (1) daily routines, (2) relationships with family members, (3) relationships with peers and (4) participation in school/work and community activities. Methods & Procedures Five youths (16–25 years) and three family members participated in this arts‐based reflexive collective case study. Ecocultural theory provided the theoretical framework for study design, data collection and analysis. Cases consist of (1) pre‐interview demographic information, (2) three 60–90‐min virtual interviews, (3) optional family member interviews, (4) multi‐media arts‐based participant‐generated materials representing participants’ experiences of communication change and concussion, and (5) researcher observations, discussions and reflexive journal entries. Reflexive thematic analysis was used to analyse the data. Outcomes & Results Analysis yielded four themes that illustrate the ways youth navigated and adapted to post‐concussion communication changes: (1) navigating changes in communication tasks, daily roles, and identity; (2) re‐negotiating relationships and emotional reactions; (3) seeking control and learning to let go during recovery; and (4) helping youth adapt to post‐concussion communication changes. Conclusions & Implications The study findings deepen our understanding of the impact of post‐concussion communication changes on youths' daily lives and underscore considerations critical to the development of communication‐focused concussion education programs and interventions tailored specifically for youth. What this paper adds What is already known on the subject Youth is a critical period of social and emotional development. Communication is integral to identity, relationships, participation in daily activities and well‐being. Concussions can affect speech clarity, fluency, understanding and use of language, and social interactions. Re‐engaging in routine activities and pre‐injury roles can be challenging for youth experiencing communication changes as part of complex concussion recoveries. What this paper adds to the existing knowledge Findings from this research illuminate how youth navigate and adapt to communication changes post‐concussion and support the development of youth‐focused communication education programs, assessments and interventions. Youth participants actively managed their recoveries by developing innovative strategies to support their communication during daily activities, learning about communication, practicing communication tasks sequentially, and facing fears. Youth also reframed and challenged narrow views of ‘normal communication’. What are the potential or actual clinical implications of this work? Findings highlight the need for more youth‐ and communication‐focused education materials and programs within youth concussion management protocols. Information about the specific ecological and sociocultural factors youth encounter during concussion recovery is needed to develop targeted communication‐focused education and intervention programs for youth and their families to mitigate risks of isolation, loneliness, and mental health concerns and increase youths’ participation in family, community and cultural life. By learning from youth about how communication changes affected their participation in daily activities, identity and relationships, clinicians can provide information and interventions to reduce adverse listener reactions and help young people feel supported and understood.